The role of branchial and orobranchial O-2 chemoreceptors in the control of aquatic surface respiration in the neotropical fish tambaqui (Colossoma macropomum): progressive responses to prolonged hypoxia - Florindo, L. H.; Leite, CAC; Kalinin, A. L.; Reid, S. G.; Milsom, W. K.; Rantin, F. T. (Company of Biologists Ltd, 2006)
The present study examined the role of branchial and orobranchial O-2 chemoreceptors in the cardiorespiratory responses, aquatic surface respiration (ASR), and the development of inferior lip swelling in tambaqui during prolonged (6 h) exposure to hypoxia. Intact fish (control) and three groups of denervated fish (bilateral denervation of cranial nerves IX+X (to the gills), of cranial nerves V+VII (to the orobranchial cavity) or of cranial nerves V alone), were exposed to severe hypoxia (Pw(O2) = 10 mmHg) for 360 min. Respiratory frequency (fR) and heart rate (fH) were recorded simultaneously with ASR. Intact (control) fish increased fR, ventilation amplitude (V-AMP) and developed hypoxic bradycardia in the first 60 min of hypoxia. The bradycardia, however, abated progressively and had returned to normoxic levels by the last hour of exposure to hypoxia. The changes in respiratory frequency and the hypoxic bradycardia were eliminated by denervation of cranial nerves IX and X but were not affected by denervation of cranial nerves V or V+VII. The VAMP was not abolished by the various denervation protocols. The fH in fish with denervation of cranial nerves V or V+VII, however, did not recover to control values as in intact fish. After 360 min of exposure to hypoxia only the intact and IX+X denervated fish performed ASR. Denervation of cranial nerve V abolished the ASR behavior. However, all (control and denervated (IX+X, V and V+VII) fish developed inferior lip swelling. These results indicate that ASR is triggered by O-2 chemoreceptors innervated by cranial nerve V but that other mechanisms, such as a direct effect of hypoxia on the lip tissue, trigger lip swelling.
Keywords: cardiorespiratory reflex; hypoxia; O-2 chemoresponse; respiratory frequency; heart frequency; ASR; inferior lip swelling; Colossoma macropomum